Mappanre temme: Meaning Construction of Khatam Al-Qur’an Tradition in Buginese Community of South Sulawesi - Abdul Rahman; Nurlela Nurlela; Firdaus W. Suhaeb (UIN Sunan Gunung Djati Bandung, 2022)
This research is motivated by the presence of the community tradition of Bulutellue, Sinjai, South Sulawesi which is inherited from generation to generation. This tradition is known as mappanre temme, which is a crowded event related to expressions of gratitude and joy by families because their children have successfully finished reading the Koran. The purpose of this study is to explain the position of the Koran in the socio-cultural space, the implementation and function of mappanre temme for the people of Bulutellue, Sinjai, South Sulawesi. The research method used is qualitative research using a religious anthropological approach. Data were collected through observation, interviews and documentation. The data that has been collected is then analyzed so that it has the ability to read the verses contained in the Koran. The results of the study indicate that in the Bulutellue Village community, the Koran is normatively interpreted as the word of God that gives instructions for the path of salvation in this world and in the hereafter. However, in terms of cultural reality, the Koran is interpreted as a special object that is sacred and contains supernatural powers so that it can be functioned as a repellent against evil, healing disease, and fertilizing plants. This function is a trigger to learn the Koran, and if you are successful in completing the Koran and have the skills to read it, the mappanre temme tradition is carried out as an expression of gratitude while maintaining social harmony and friendship between community members, village government officials, and religious officials, as well as maintain and strengthen the relationship between students and teachers of the Koran.